Essential statistics exploring the world through data - Gould, Robert 1965-; Ryan, Colleen N. (Colleen Nooter) 1939-; Wong, Rebecca (Rebecca Kimmae) (Pearson Education Limited, 2017)
The primary focus of this text is still, as in the first edition, data. We live in a datadriven economy and, more and more, in a data-centered culture. We don't choose whether we interact with data; the choice is made for us by websites that track our browsing patterns, membership cards that track our spending habits, cars that transmit our driving patterns, and smart phones that record our most personal moments